The Implementation of Family Planning program during the COVID-19 Pandemic: Scoping Review - Hutari Puji Astuti; Andari Wuri Astuti; Askuri (PT Inovasi Pratama Internasional, 2023)
Background:The family planning program in Indonesia has been started since 1957, but it was merely part of health issues. With the increasing population of Indonesian people, the high maternal mortality rate, and the need for reproductive health, family planning programs are then used as a way to suppress population growth and improve maternal and child health. According to the National Population and Family Planning Board (BKKBN), the primary problem in actualizing the target of family planning programs is the low participation of couples of childbearing age (EFA). Another problem currently emerging is the increasing number of family planning dropouts as a direct impact of the COVID-19 pandemic. Purpose: This study aimed to scrutinize the implementation of family planning programs during the COVID-19 pandemic. Methods: The method in this research was scoping review. The literature search in this study used 3 health journal databases, namely PubMed, ScienceDirect, ProQuest, and 1 search engine: Google Scholar. Articles were selected using inclusion criteria, which were Articles published in national and international journals from 2019 to 2021. The total search results were 274 articles, and 9 articles were found that met the inclusion criteria in the author's review. The instruments used to assess the quality of articles was The Joanna Briggs Institute (JBI) Critical Appraisal Tools.Results:The impact of family planning services in the COVID-19 pandemic era is a decrease in family planning participants in March 2020 when compared to February 2020 throughout Indonesia. Factors that affect family planning program services during the COVID-19 pandemic include : knowledge, Husband’s support, Support from health professionals. Conclusions:The conclusion from the nine articles is that several countries have experienced changes in the system of maternal and child health services and family planning services. Many countries encountered a decrease in family planning participants and the presence of unwanted pregnancies.